TECHNOLOGY OF ORGANIZING INDEPENDENT EDUCATION OF STUDENTS IN MATHEMATICS (ResearchJet Journal of Analysis and Inventions, 2023)
This article contains recommendations on how to organize the educational process on the basis of advanced pedagogical and modern information technologies, as well as on how to achieve high qualifications using teaching methods